ANALISIS KEMAMPUAN HIGHER ORDER THINKING SKILLS (HOTS) DALAM PEMBELAJARAN IPA KELAS V DI SEKOLAH DASAR - Indriyana, Niana; Indah Wardatussa’idah; Prayuningtyas Angger WardhaniIndah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was carried out to determine students’ high-level thinking abilities in ntural Science lessons in elementary schools. In this ever-growing 21st century, students need abilities in learning, namely high-level thinking, students must applys cience learning based on Higher Order Thinking Skills (HOTS), which is a student thinking process with a higher cognitive level developed from various learning taxonomy concepts such as Bloom’s taxonomy, learning taxonomy, teaching and assessment. The aim of students implementing HOTS is to improve students’ ability to think critically at a higher level. This type of research is qualitative research using the literature study method. The result is that implementing HOTS-based learning in high school elementary schools trains students abilities to think critically, creatively, and solve their own problems with the knowledge they have. Penelitian ini dilaksanakan untuk mengetahui kemampuan berpikir tingkat tinggi siswa pada pelajaran Ilmu Pengetahuan Alam (IPA) di sekolah dasar. Dalam abad 1 yang terus berkembang ini, siswa membutuhkan kemampuan dalam pembelajaran yaitu cara berpikir tingkat tinggi, maka siswa harus menerapkan pembelajaran IPA berbasis Higher Order Thinking Skills (HOTS), yang merupakan proses berfikir siswa dengan level kognitif yang lebih tinggi yang dikembangkan dari berbagai konsep taksonomi pembelajaran seperti taksonomi Bloom, taksonomi pembelajaran, pengajaran dan penilaian. Tujuan dari siswa menerapkan HOTS, yaitu agar meningkatkan kemampuan siswa dalam berfikir kritis pada level yang lebih tinggi. Jenis penelitian ini yaitu penelitian kualitatif dengan metode studi literatur. Hasilnya dengan menerapkan pembelajaran berbasis HOTS di SD kelas tinggi melatih kemampuan siswa untuk berpikir kritis, kreatif, memecahkan masalah sendiri dengan pengetahuan yang dimiliki.